(untitled) (Baghdad Science Journal, 2025)
The effect of the aqueous extract of fig (Ficus carica) fruit was studied by using different concentrations of this fruit (15, 20 and 25 mg/kg of body weight) on some hematological parameters (hemoglobin concentration, packed cell volume, white blood cell count and platelets count) in female rabbits. Twenty female rabbits were randomly divided into four groups (five animals in each group). Three groups were dosed with the concentrations mentioned above, while the last was administered with distilled water and considered as control group. These animals were orally dosed by aqueous extract using a micropipette. The results showed that there was a significant (P